Colorectal Cancer: Causes and Evidence of Chemopreventive Treatments - Pérez-Escalante, Emmanuel; Cariño-Cortés, Raquel; Fernández-Martínez, Eduardo; Ortiz, Mario I.; Muñoz-Pérez, Víctor M.; Sánchez-Crisóstomo, Isabel; Jiménez-Ángeles, Luis (Current Pharmaceutical Biotechnology, 2018)
Background: Colorectal cancer (CRC) is the second and third most frequent cancer in women and men, respectively; indeed, CRC is placed as the fourth world's most deadly cancer (after lung, liver, and stomach cancer). The incidence of CRC is strongly influenced by nutrition and the high fat/high carbohydrate Western-style diet. CRC is one of the most intensively studied cancer types, partly because of its high prevalence, but also because of the existence of its precursor lesions, tubular or villous adenomas, and more recently serrated adenomas. The morphological steps in the adenomacarcinoma sequence have been elucidated at a molecular level, which allow the identification of the genes responsible for CRC. Review and Conclusions: The main aim of this review is to provide data regarding the pathophysiological characteristics, molecular mechanisms as well as carcinogenic and chemopreventive agents for CRC, with emphasis on evidence supporting their efficacy. These compounds may modulate multiple signaling pathways involved in cell proliferation and apoptosis in transformed cells, they also enhance the host immune system and favor an effective treatment. Despite promising results from experimental studies, only a limited number of these compounds have been tested in clinical trials. The mechanistic spectrum and specificity of the action of phytochemicals represent a complex and evolving field of research.
Keywords: natural compounds